Long-Term Retention of Diverse Paleontologists Requires Increasing Accessibility - Carter, Aja Mia; Johnson, Erynn H.; Schroeter, Elena R. (Frontiers in Ecology and Evolution, 2022)
Geoscience encompasses a variety of scientific subdisciplines aimed at exploring, understanding, and predicting global phenomena. Yet despite its global reach, the geosciences are the least diverse of the STEM disciplines. Paleontology, a subdiscipline which prides itself on unearthing the diversity of life, comprises no greater level of diversity among its researchers than geosciences overall. This deficiency is in direct opposition to the level of public interest generated by paleontological research. Paleontology has broad educational appeal and has been leveraged in various ways to promote STEM learning. However, despite this widespread interest, there is an overwhelming decrease in the diversity of participants in paleontology at increasing levels of academia. At each academic career stage, from undergraduate to tenured faculty, the number of underrepresented (URP) and underserved persons (USP) dwindles. Here we highlight and discuss barriers to access experienced by URP and USP researchers that hinder their ability to progress at every level of the academic journey post-K-12, focusing on the track to a tenured professorship. Neglecting to consider the unique barriers faced by URPs and USPs when developing curricula, building programs, and evaluating productivity perpetuates the chronic lack of diversity in paleontology, regardless of individual interest in pursuing a career in the field. We also suggest actionable items for instructors, as well as members of the scientific community in positions of power and policymakers. While the lack of diversity in paleontology is dire, the field is small enough that individuals have the potential to make a meaningful difference.